Reduction in chromosome mobility accompanies nuclear organization during early embryogenesis in Caenorhabditis elegans - Ritsuko Arai (Nature Portfolio, 2017)
Abstract In differentiated cells, chromosomes are packed inside the cell nucleus in an organised fashion. In contrast, little is known about how chromosomes are packed in undifferentiated cells and how nuclear organization changes during development. To assess changes in nuclear organization during the earliest stages of development, we quantified the mobility of a pair of homologous chromosomal loci in the interphase nuclei of Caenorhabditis elegans embryos. The distribution of distances between homologous loci was consistent with a random distribution up to the 8-cell stage but not at later stages. The mobility of the loci was significantly reduced from the 2-cell to the 48-cell stage. Nuclear foci corresponding to epigenetic marks as well as heterochromatin and the nucleolus also appeared around the 8-cell stage. We propose that the earliest global transformation in nuclear organization occurs at the 8-cell stage during C. elegans embryogenesis.